Understanding adolescents’ experience with an unwanted pregnancy / Azmawaty Mohamad Nor - Azmawaty, Mohamad Nor (2015)

(untitled)
Adolescence pregnancy is a global dilemma. It is by no means a new occurrence but a continuing issue that needs to be attended to, in the context of the Malaysian society. Aiming to contribute to the body of knowledge in addressing ways to curb the issue, the study focused in gaining an in-depth understanding of the adolescents’ experience with an unwanted pregnancy. It is important to note that the purpose of study has only been to find out how the adolescents in this study made sense of their experience without any external interference of counseling elements. The Interpretative Phenomenological Analysis (IPA), a qualitative approach is used to explore the experiences of purposively sampled four unmarried adolescents between 16 to 18 years old. The data collection process involved a series of three, in-depth interviews with each participant focusing on the life history, current experience and reflection on the experience. A total of 23 indepth interview sessions were carried out with each session ranging from 40 to 90 minutes. Other forms of data collection were also obtained via observations and documents such as diaries, drawings, field notes and the researcher’s reflexive notes. Data analysis were based on Smith’s (2009) six-step analysis in IPA. The consequences of an unwanted pregnancy have an impact on the participants’ psychological make-up. However, the sense making of the experience is unique to each of the participants. The participants’ journey with an unwanted pregnancy was an “experience” of importance when they reflected on the significance of what had happened and engaged cognitively in making sense of that “experience”, whence seven (7) themes emerged. The seven themes were: “search for fun, freedom and love”, “abortion attempts”, “emotional numbing”, “spiritual strengthening”, “transformation from unwanted to wanted pregnancy”, “transformation of self” and “sexuality education”. The themes uncovered that the participants have transformed from a sense of hopelessness to a hopeful future. iv The turning point of transformation and the emotional journey are unique to each of the participants. Crisis counseling and effective counseling methods applied in the helping professionals practice are important to facilitate and to enhance this positive transformation. Additionally, outcomes of the research may provide further insights to the policy makers in formulating better and more effective policies in tackling unwanted pregnancies among adolescents. The study also indicated there is room for a better preventive program and healing process to be promulgated and implemented.